2017
DOI: 10.1371/journal.pone.0189861
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-specific ablation of the E3 ubiquitin ligase Mdm2 leads to oxidative stress, broad mitochondrial deficiency and early death

Abstract: The maintenance of normal heart function requires proper control of protein turnover. The ubiquitin-proteasome system is a principal regulator of protein degradation. Mdm2 is the main E3 ubiquitin ligase for p53 in mitotic cells thereby regulating cellular growth, DNA repair, oxidative stress and apoptosis. However, which of these Mdm2-related activities are preserved in differentiated cardiomyocytes has yet to be determined. We sought to elucidate the role of Mdm2 in the control of normal heart function. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 161 publications
(176 reference statements)
0
32
0
Order By: Relevance
“…Several studies have recently shown that MDM2 is associated with rheumatoid arthritis (RA), an autoimmune disorder that causes chronic inflammation and injury of the joints and other organs in the body and the major findings are summarized in Figure . For instance, Assmann et al have examined the roles of two functional single nucleotide polymorphisms (SNPs), MDM2 SNP309 and p53 P72R, in patients who fulfill the American College of Rheumatology criteria for RA.…”
Section: Roles Of Mdm2 In Inflammation and Autoimmune Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have recently shown that MDM2 is associated with rheumatoid arthritis (RA), an autoimmune disorder that causes chronic inflammation and injury of the joints and other organs in the body and the major findings are summarized in Figure . For instance, Assmann et al have examined the roles of two functional single nucleotide polymorphisms (SNPs), MDM2 SNP309 and p53 P72R, in patients who fulfill the American College of Rheumatology criteria for RA.…”
Section: Roles Of Mdm2 In Inflammation and Autoimmune Diseasesmentioning
confidence: 99%
“…HF is a chronic and progressive condition that is characterized by the inability of the heart to pump an adequate supply of blood . Hauck et al have reported that MDM2 expression is significantly downregulated at the mRNA level in heart tissue samples from patients with idiopathic dilated cardiomyopathy (DCM), ischemic cardiomyopathy, and chemotherapy‐induced cardiomyopathy (Figure ). Similarly, acute cardiac‐specific ablation of MDM2 causes pathological cardiac hypertrophy and early death in an MDM2 f/f ; mcm conditional mutant mouse model .…”
Section: Roles Of Mdm2 In Hf and Cardiovascular Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The key finding of this study is that E3 ubiquitin ligase Mdm2 plays a direct role in mitophagy by regulating the activity of another E3 ubiquitin ligase, parkin, discovered via its genetic link to PD, as the name implies. Although the role of Mdm2 in mitochondria function was proposed earlier 66 , in that study Mdm2 appeared to act via ubiquitination of its well-established substrate, p53. Another reported mitochondria-related function of Mdm2 was not connected with p53 ubiquitination, involving instead its import into these organelles, where Mdm2 appears to repress the transcription of NADH-dehydrogenase 6, inhibiting respiratory complex I activity 51 .…”
Section: Discussionmentioning
confidence: 85%